PENERAPAN MODEL PEMBELAJARAN CARD SORT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SDN 024 MUNSALO KOPAH KECAMATAN KUANTAN TENGAH - Ernedisman Ernedisman (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to improve the learning outcomes of students of grade IV of SD Negeri 024 Munsalo Kopahthrough "application of learning model card sort". This study uses classroom action research that is an actionresearch done with the aim of improving learning outcomes in the classroom. The purpose of this study is tosolve real problems, teachers in their professional development activities are examined about teacher activity,student activities based on very good category, good, enough, and less, which is studied is the result of learningCivics. Based on the results of data analysis in this study, it can be concluded that: The average activity of firstcycle cycle I meeting is 66.67 with enough category, the second meeting 70,83 with enough category. In thesecond cycle of the first meeting 83.33 with good category, the second meeting 87.53 with good category. Whilethe average of student activity on the first cycle of the first meeting 62.5 with enough category, the secondmeeting 66.67 with Enough category. In the second cycle of the first meeting 79.17 with good category, at thesecond meeting 83.33 with good category. On the learning outcomes the average acquisition of UAS I is 70.20.on UAS II with an average of 90.25. Thus it can be concluded that the application of the learning model of cardsort can improve the learning outcomes of Civics students grade IV of SD Negeri 024 Munsalo Kopah.